Protostars and planets V - Reipurth, Bo.; Jewitt, D. (David); Keil, Klaus (Tucson : University of Arizona Press, 2007)
Increasing discoveries of new planets beyond our solar system are invigorating the quest for new knowledge and understanding of the birth of stars and planets. This new volume in the Space Science Series, with 249 contributing authors, builds on the latest results from recent advances in ground and space-based astronomy and in numerical computing techniques to offer the most detailed and up-to-date picture of star and planet formation, including the formation of our own solar system. This book emphasizes the cross-disciplinary aspects of the field, with a particular focus on the early evolution of our solar system. Protostars and Planets V is the new foundation for further advancement in the fields of stellar and planetary formation, making it an indispensable resource for researchers and students in astronomy, planetary science, and the study of meteorites.
"The Protostars and Planets V conference was held at the Hilton Waikoloa Village on the Big Island of Hawaii on October 24-28, 2005"--Pref.
Includes bibliographical references and index.
Keywords: Protostars -- Congresses; Planetary science -- Congresses; Meteorites -- Congresses